PENDIDIKAN DAN MANDOK HATTA ETNIK BATAK TOBA - Syawal, Hasanul; Marsa, Yummy Jumiati (Islamijah: Journal of Islamic Social Sciences, 2025)
This study explores the profound role of Mandok Hata, a traditional Batak Toba oral custom, as socio-cultural capital in fostering holistic educational development within the Batak Toba society. Moving beyond conventional formal learning paradigms, this research posits that Mandok Hata serves as a crucial indigenous pedagogical tool, transmitting values, ethics, historical knowledge, and social norms across generations. Through an ethnographic approach, this study investigates how the practice of Mandok Hata cultivates essential life skills, critical thinking, and a strong sense of community identity among Batak Toba youth, thereby complementing and enriching formal education. Findings reveal that the intricate layers of symbolism, rhetoric, and performativity inherent in Mandok Hata contribute significantly to the development of communicative competence, emotional intelligence, and cultural resilience. This research argues for the recognition and integration of such local wisdom practices into contemporary educational frameworks to achieve a more culturally relevant and holistic educational development that honors indigenous heritage while preparing individuals for modern challenges. Keywords: Mandok Hata, Local Wisdom, Batak Toba, Holistic Education